Handbook of radioactivity analysis. - L'Annunziata, Michael F. (Academic Press, 2020)
Handbook of Radioactivity Analysis: Radiation Physics and Detectors, Volume One, and Radioanalytical Applications, Volume Two, Fourth Edition, is an authoritative reference on the principles, practical techniques and procedures for the accurate measurement of radioactivity - everything from the very low levels encountered in the environment, to higher levels measured in radioisotope research, clinical laboratories, biological sciences, radionuclide standardization, nuclear medicine, nuclear power, and fuel cycle facilities, and in the implementation of nuclear forensic analysis and nuclear safeguards. It includes sample preparation techniques for all types of matrices found in the environment, including soil, water, air, plant matter and animal tissue, and surface swipes. Users will find a detailed discussion of our current understanding of the atomic nucleus, nuclear stability and decay, nuclear radiation, and the interaction of radiation with matter relating to the best methods for radionuclide detection and measurement. Spans two volumes, Radiation Physics and Detectors and Radioanalytical Applications Includes a much-expanded treatment of calculations required in the measurement of radionuclide decay, energy of decay, nuclear reactions, radiation attenuation, nuclear recoil, cosmic radiation, and synchrotron radiation Includes the latest advances in liquid and solid scintillation analysis, alpha- and gamma spectrometry, mass spectrometric analysis, gas ionization and nuclear track analysis, and neutron detection and measurement Covers high-sample-throughput microplate techniques and multi-detector assay methods.